Negotiating Religious Moderation: Qur'anic Interpretation And The Construction Of Wasatiyyah Discourse In Indonesia - Syamsuni, Syamsuni (PT. Sharia Journal and Education Center, 2026)
This article examines the construction and negotiation of wasatiyyah (Islamic moderation) discourse in Indonesia through Qur'anic interpretation as a complex socio-religious phenomenon. Drawing on discourse analysis and critical examination of contemporary tafsir literature, this study demonstrates that wasatiyyah is not a static theological concept but a contested discursive space negotiated among state institutions, Islamic scholars, civil society organizations, and digital platforms. The analysis reveals that while wasatiyyah discourse is promoted as an authentic Islamic principle grounded in Qur'anic teachings particularly the concept of